2018
DOI: 10.1007/s00429-018-1764-4
|View full text |Cite
|
Sign up to set email alerts
|

Unidirectional monosynaptic connections from auditory areas to the primary visual cortex in the marmoset monkey

Abstract: Until the late twentieth century, it was believed that different sensory modalities were processed by largely independent pathways in the primate cortex, with cross-modal integration only occurring in specialized polysensory areas. This model was challenged by the finding that the peripheral representation of the primary visual cortex (V1) receives monosynaptic connections from areas of the auditory cortex in the macaque. However, auditory projections to V1 have not been reported in other primates. We investig… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 107 publications
1
22
0
Order By: Relevance
“…Assignment of penetrations to these subdivisions of auditory cortex was based on converging evidence from electrophysiological mapping of responses to pure tones (cochleotopic organization) and histological examination of the electrode tracks. As reported previously in marmoset auditory cortex (Aitkin and Park, 1993; Nelken et al, 1999; Kajikawa et al, 2005; Bendor and Wang, 2008; Mesgarani et al, 2014), we found a cochleotopic low-to-high CF gradient from rostral to caudal A1 (Figure 1A) and a reversal of this gradient in the roughly 1 mm wide region of the caudal belt; penetrations further caudal to CM did not contain units responsive to either tones or vocalizations (Figure 1A), indicating this is likely not part of auditory cortex (Majka et al, 2018). Our results are in line with parcellation into core, belt and parabelt auditory cortical areas on the basis of the tuning characteristics of neurons in sites assigned to these subdivisions (Figures 1B,C) and latency of responses to tones and vocalizations (e.g., Figures 1D, 2).…”
Section: Resultsmentioning
confidence: 65%
See 1 more Smart Citation
“…Assignment of penetrations to these subdivisions of auditory cortex was based on converging evidence from electrophysiological mapping of responses to pure tones (cochleotopic organization) and histological examination of the electrode tracks. As reported previously in marmoset auditory cortex (Aitkin and Park, 1993; Nelken et al, 1999; Kajikawa et al, 2005; Bendor and Wang, 2008; Mesgarani et al, 2014), we found a cochleotopic low-to-high CF gradient from rostral to caudal A1 (Figure 1A) and a reversal of this gradient in the roughly 1 mm wide region of the caudal belt; penetrations further caudal to CM did not contain units responsive to either tones or vocalizations (Figure 1A), indicating this is likely not part of auditory cortex (Majka et al, 2018). Our results are in line with parcellation into core, belt and parabelt auditory cortical areas on the basis of the tuning characteristics of neurons in sites assigned to these subdivisions (Figures 1B,C) and latency of responses to tones and vocalizations (e.g., Figures 1D, 2).…”
Section: Resultsmentioning
confidence: 65%
“…Allocation of penetrations to these fields was done principally on the basis of the reliable changes in tonotopic sequence across auditory cortex (as also seen in other animals not part of this study), and on the physiological response characteristics (e.g., FRA bandwidth, response latency, response duration). Additionally, in some cases, comparisons of the histology of auditory cortex were made to our other work (Majka et al, 2018). To ensure we obtained good quality data for all fields, we recorded from no more than 3 fields in any animal.…”
Section: Methodsmentioning
confidence: 99%
“…We were able to combine subsets of the injections placed in this study with injections in previous studies, as well as data gathered in collaborating laboratories, to generate and test specific hypotheses, indicating the utility of the data gathered in the project (Lee et al, 2018; Majka et al, 2018). In addition, analysis of injection centers show proximity/overlap of injections from a previous data set from the Rosa laboratory for which 3D spatial information is available (Appendix 10).…”
Section: Discussionmentioning
confidence: 83%
“…This is discussed further in the next subsection. This approach of combining our project injections with data from other investigators has already led to collaborative publications (Huo et al, 2018; Majka et al, 2018).…”
Section: Mri Methodsmentioning
confidence: 96%
“…This finding is in line with previous observations in ferrets (Cantone et al, 2005;Dell et al, 2019), and primates (Kennedy and Bullier, 1985;Perkel et al, 1986;Barone et al, 1995) which reveal that the area immediately rostral to a given area supplies the majority of feedback. We did not observe any label in auditory cortex rostral to the Ssy sulcus as our injections may not have been peripheral enough (Falchier et al, 2002;Majka et al, 2019). We did not systematically investigate connections at different eccentricities so we cannot compare to other studies (Palmer and Rosa, 2006).…”
Section: Comparison With Feedback Circuits To Area 17 In the Ferret mentioning
confidence: 90%